Peran Pondok Pesantren dalam Pengembangan Jiwa Islamic Enterpreneurship: ( Studi Pada Pondok Pesantren Al- Inayah Di Rimbo Bujang) - Dwi Nurul Fatwa; As’ad Isma; Anzu Elvia Zahara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This thesis is intended to find out how the role of Islamic boarding schools in the development of entrepreneurship in students. As the goal is how it will affect if iwa enterpreneusrhip is applied to students. In this study, a qualitative approach method is used with a data collection method by conducting, observing, interviewing, and drawing conclusions. The results of drawing conclusions are as follows: (1) Al Inayah Islamic boarding school provides several business unit facilities as a practice for student development, although not all business units can be managed directly by students, but the entrepreneurial development carried out by the pesantren is quite ideal. Because pesantren has provided learning methods and the basics of entrepreneurship to students. (2) Students begin to be able to manage and capitalize on their own businesses, through the provision of entrepreneurship and vocational practices as a support for the Islamic spirit of entrepreneurship of students and of course under the supervision and direction of the management and the board of teachers of Islamic boarding schools. But not all pesantren business units can be used efficiently, because there are indeed several business units that specifically help students only if needed. (3) In its role, pesantren has provided balanced entrepreneurship provisions to students with pesantren backgrounds, of course, in providing knowledge about entrepreneurship, pesantren equipping religious knowledge as a guideline for Muslim entrepreneurs. In the form of pesantren training, it also holds seminars by bringing in experts or resource persons in entrepreneurship and the provision of BLK (Job Training Center) that can be participated by students.